Effects and toxicity of Eugenia punicifolia extracts in streptozotocin-diabetic rats - Brunetti, Iguatemy Lourenço [UNESP]; Vendramini, Regina Célia [UNESP]; Januario, A. H.; Franca, S. C.; Pepato, Maria Teresa [UNESP] (Taylor & Francis Inc, 2006)
Extracts and decoctions of Eugenia jambolana Lam., Eugenia uniflora L., and Eugenia punicifolia (Humb., Bonpl. & Kunt) DC. are used in traditional medicine to treat diabetes mellitus. Although there have been reports that Eugenia jambolana and Eugenia uniflora have antidiabetic effects, no study has yet been made on Eugenia punicifolia . We investigated the effects of aqueous, butanol, and methanol extracts of Eugenia punicifolia leaves administered by gavage to streptozotocin-diabetic rats for 26 to 29 days. Body weight, food and fluid intake, urine volume, and urinary glucose and urea were evaluated every 7 days. At the end of the experiment, we measured serum cholesterol, high-density lipoprotein (HDL)-cholesterol, triglycerides and bilirubin, hepatic glycogen and serum marker-enzymes (alanine and aspartate aminotransferases, alkaline phosphatase, gamma-glutamyltransferase, L-lactate dehydrogenase, creatine kinase, alpha-amylase, and angiotensin I converting enzyme). We found that in rats treated with the aqueous extracts, food and liquid intake, urinary volume, and body weight were all reduced, while for rats treated with the methanol extract, not only were liquid intake, urinary volume and body weight reduced, but urinary glucose and urea also decreased. Rats treated with the butanol extract showed no significant alterations in any of the parameters measured. Chronic treatment with extracts had no effect on the marker enzymes nor on serum bilirubin levels. The results indicate that aqueous extracts of Eugenia punicifolia leaves produced an anorexic effect and that methanol extracts had a beneficial effect on the diabetic state by improving carbohydrate and protein metabolism without provoking hepatobiliary, microvascular, muscular, or pancreatic toxic effects.
Keywords: antidiabetic activity; chronic treatment; Eugenia punicifolia; marker enzymes; toxicity